2003
DOI: 10.1046/j.1467-7652.2003.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

A sequence mutation in the cinnamyl alcohol dehydrogenase gene associated with altered lignification in loblolly pine

Abstract: SummaryEvidence for the molecular basis of a null allele of cinnamyl alcohol dehydrogenase (CAD) has been discovered in the loblolly pine ( Pinus taeda L.) clone 7-56. The mutation is a twobase pair adenosine insertion located in exon 5 that causes a frame-shift which is predicted to result in premature termination of the protein. For routine detection of the mutation, a diagnostic assay was developed utilizing T emplate-directed D ye-terminator I ncorporation and F luorescence P olarization detection (FP-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…A nonsynonymous substitution in exon I of cad (SNP M28) was in strong association with earlywood specific gravity. DNA sequence data showed full linkage of this SNP with another nonsynonymous substitution in exon IV ( Figure 4A; our unpublished results), and partial linkage with the cad null allele causing lignin modifications in wild trees (see Ralph et al 1997;Gill et al 2003). cad is a key enzyme in the lignin biosynthesis (2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A nonsynonymous substitution in exon I of cad (SNP M28) was in strong association with earlywood specific gravity. DNA sequence data showed full linkage of this SNP with another nonsynonymous substitution in exon IV ( Figure 4A; our unpublished results), and partial linkage with the cad null allele causing lignin modifications in wild trees (see Ralph et al 1997;Gill et al 2003). cad is a key enzyme in the lignin biosynthesis (2004).…”
Section: Discussionmentioning
confidence: 94%
“…Several of these candidate genes for wood formation have been confirmed by forward or reverse genetic mutant analyses in model species (see, for example, Goujon et al 2003 for xylem lignification in Arabidopsis) or by the study of natural mutants (see Ralph et al 1997 andGill et al 2003 for cad gene). In addition, on the basis of the pattern of DNA sequence polymorphism, Pot et al (2005) suggested a functional role in wood formation for three genes: pp1 (a glycine-rich protein), cesA3 (a cellulose synthase), and korrigan (a gene involved in cellulosehemi-cellulose assembly; Pot et al 2006), andGonzález-Martínez et al (2006b) found that ccoaomt-1, a gene involved in lignin biosynthesis, might be a target of balancing selection in natural populations of P. taeda.…”
mentioning
confidence: 99%
“…Some mutations can be detected in the haploid megagametophytes that surround the embryo in the seed of gymnosperms. For example, a null mutation in the monolignol biosynthetic gene Cad was discovered in megagametophytes and was subsequently mapped, sequenced, and characterized Ralph et al 1997;Gill et al 2003).…”
Section: Inferring Functional Roles For Genes In Trees Forward Geneticsmentioning
confidence: 99%
“…Association genetics has been applied to wood property traits (Thumma et al 2005;GonzalezMartinez et al 2006a) and the drought stress-response (Gonzalez-Martinez et al 2006b). In loblolly pine, a study of 58 SNPs in 20 wood and drought-related candidate genes found association of allelic variation in α-tubulin with earlywood microfibril angle (Gonzalez-Martinez et al 2006a). Association was also found for SNPs in two genes in the lignin biosynthetic pathway.…”
Section: Integration Of Quantitative and Molecular Genomicsmentioning
confidence: 99%
“…Although natural mutants have been identified for some traits (e.g. Gill et al, 2003), routine genetic segregation and inheritance studies are problematic in trees due to their long generation time and strong inbreeding depression.…”
Section: Introductionmentioning
confidence: 99%